Metode Bimbingan Islam Terhadap Mualaf: Studi Kasus Mualaf di Desa Trutup Kecamatan Plumpang Kabupaten Tuban - Muzayannah, Siti (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
Through this research the author intends to describe how Islamic guidance methods are carried out by Islamic religious instructors, both functional instructors and honorary instructors who are in the KUA of Plumpang sub-district. This type of research is qualitative, data collection is done by observation, interviews and documentation. The collected data were analyzed using qualitative methods and then concluded using deductive thinking methods. The results of the research show that the method of Islamic guidance carried out by Islamic Extension Counselors for converts uses the direct method, namely mentors and converts face to face and in dialogue by implementing group functions, the exemplary method through examples in behavior and practice in worship and muamalah, and the method of awareness using motivational words and also stories in the Qur'an that contain messages and educational values ​​such as stories of the Prophets and pious people.